Associations of Gut Microbiota with Osteoporosis in Elderly Chinese: A Cohort Study. (29th May 2020) - Ling, Chu-Wen; Miao, Ze-Lei; Zhou, Hong-Wei; He, Yan; Zheng, Ju-Sheng; Chen, Yu-Ming
Abstract: Objectives: The objective was to characterize the gut microbiome in cross-sectional and prospective connection to the development of osteoporosis. Methods: The study was embedded in the Guangzhou Nutrition and Health Study (GNHS). Data with 1776 participants for the cross-sectional study was from the second follow-up, 517 participants of whom during the third follow-up (a mean of 3.2 years after the second follow-up) were included in the longitudinal study. Gut microbiota was determined using 16S amplicon sequencing during the second follow-up, while the examination of osteoporosis was performed using a dual energy X-ray absorptiometry during the second and third follow-up. We used LDA Effect Size to investigate the cross-sectional association of gut microbiota with osteoporosis and we constructed microbe scores with identified microbe biomarkers and integrated their main functional modules associated with osteoporosis with multiple linear regression. We then examined the association of microbe scores with change in the degree of osteoporosis using logistic regression. Results: β -diversity of gut microbiota was associated with osteoporosis. Lumbar spine osteoporosis was associated with 2 genus, while femoral neck osteoporosis was associated with 10 genus. The microbe scores showed cross-sectional positive associations with osteoporosis and the microbe score-osteoporosis associations with same direction were showed in the longitudinal study. The microbiomes of participants with lumbar spine osteoporosis contained more genes that were related to peptidases, while femoral neck osteoporosis was positively associated with transcription machinery. Conclusions: These analyses provide the largest and detailed cross-sectional and longitudinal composition and functional profile of the gut microbiome in osteoporosis. Funding Sources: National Natural Science Foundation of China, Westlake University and Sun Yat-sen University.